Balancing Local and Foreign Languages: Family Language Policy in Multicultural Samarinda - Lubis, Indah Sari; Siregar, Bahren Umar; Manara, Christine (Studies in English Language and Education, 2025)
This study investigates the interaction between local, national, and foreign languages in family language policies in Samarinda, Indonesia. The main focus is on how these policies affect social cohesion and educational opportunities. The study emphasises a notable deficiency in comprehending the manner in which multilingual policies are managed inside the household in multicultural environments. This research utilised a qualitative case study methodology to investigate language practices and attitudes in 10 multilingual families in Samarinda. The investigation involved conducting in-depth interviews and participant observation. The results demonstrate that these families effectively handle language usage, striking a balance between preserving their culture and meeting the linguistic requirements of a globalised world. This, in turn, promotes social integration and improves economic prospects. The careful management of languages within family settings indicates that comprehensive and adaptable language policies are essential for promoting social unity and expanding opportunities for education and economic participation. It provides both theoretical and practical contributions to the discussion on family language policies, delivering valuable insights that may be used to improve policy-making in similar multicultural settings. This research not only expands scholarly comprehension of linguistic dynamics in multicultural environments but also offers practical suggestions for policymakers to promote linguistic diversity and enhance availability of language resources.